Persoalan Privasi dan Degradasi Martabat Manusia dalam Pengawasan Berbasis Kecerdasan Buatan (AI): Privacy Issues and Degradation of Human Dignity in Artificial Intelligence (AI) Based Surveillance - Pabubung, Michael Reskiantio (Jurnal Filsafat Indonesia, 2024)
The digital era is like two sides of a coin that have two different impacts: positive and negative. One of the negative impacts is the violation of privacy, especially in the application of artificial intelligence technology. Artificial intelligence technology requires data as its fuel. The need for data is pivotal because artificial intelligence algorithms operate based on [collected] data. As a result, the demand for data has had an impact on humans, where individual information is collected for unrevealed purposes. Often, interested parties argued for security and order reasons. Some gave no reasons because people usually do not object to the data they submit. Why is the issue of privacy essential and urgent to study in the context of AI surveillance? Through qualitative methods with literature analysis techniques in Kantian philosophical perspectives, the author concludes that privacy is quintessential for human dignity. Hence, violating privacy through AI surveillance is a case of humanity because it degrades human dignity.